2017
DOI: 10.9753/icce.v35.waves.21
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Partitioning and Swells in the Black Sea

Abstract: The swell climate of the Black Sea has been determined using a long-term 31-year wave hindcast with the third-generation spectral wave model SWAN in combination with spectral partitioning. This technique enables decomposing wave spectra into individual wave systems representing wind seas or swells and computing integral wave parameters of each partition. Results are presented of the partition technique and of spatial and seasonal characteristics of wind sea and swell systems. In addition, the average amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…The average swell weight was below 0.4 (Fig. 3a), which is slightly higher than the winter average for the Black Sea (0.3, Van Vledder and Akpınar, 2016), but lower than in the World Ocean (over 0.5, Semedo et al, 2011). The Baltic Sea swell climate also differs from the World Ocean by typically being very short (under 5 s, Fig 4).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The average swell weight was below 0.4 (Fig. 3a), which is slightly higher than the winter average for the Black Sea (0.3, Van Vledder and Akpınar, 2016), but lower than in the World Ocean (over 0.5, Semedo et al, 2011). The Baltic Sea swell climate also differs from the World Ocean by typically being very short (under 5 s, Fig 4).…”
Section: Discussionmentioning
confidence: 88%
“…More elaborate schemes that are capable of identifying several swell systems have been developed (e.g. Portilla et al, 2009), and such methods have been tested in the Black Sea by (Van Vledder and Akpınar, 2016). We found that in the Baltic Sea even ECMWF's simple partitioning flagged a minimal amount of energy as swell during the growth phase of the the wave field, resulting in spurious non-zero swell weights (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In enclosed or semi-enclosed seas the swell climate is completely detached from the global swell conditions (Berkun, 2007;Van Vledder and Akpınar, 2017;Divinsky and Kosyan, 2018). One such semi-enclosed sea is the Baltic Sea, which is only connected to the ocean through the narrow and shallow Danish straits, through which no significant amount of swell can propagate.The small size of the Baltic Sea naturally limits the severeness of its swell climate compared to the oceans, and waves classified as swell might often not coincide with the above-mentioned conceptual definition.…”
Section: Introductionmentioning
confidence: 99%
“…For synoptic conditions of the Black Sea, this discreteness is clearly inadequate and the results obtained can be regarded as highly estimated. One of the recent works is the study [10], in which the authors used the capabilities of the SWAN model updated version for automatic separation of wave components. The result of the work was the climatic fields of wind-induced waves and swell for the Black Sea basin for 4 seasons.…”
mentioning
confidence: 99%